PENINGKATAN HASIL BELAJARSISWA DENGAN MENERAPKAN MODEL PEMBELAJARAN INKUIRI PADA SISWA KELAS IV SD KRISTEN NYAMA - Lellolsair, Elsi; Septory, Jekriel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning outcomes of elementary school students remain a common problem in the learning process. This condition is generally caused by the use of instructional models that do not actively engage students, resulting in passive learning and limited conceptual understanding. One instructional model that has the potential to enhance students’ activeness and critical thinking skills is the inquiry-based learning model. This study aimed to improve the learning outcomes of fourth-grade elementary school students through the implementation of an inquiry-based learning model. This study employed Classroom Action Research conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The research participants were fourth-grade elementary school students. Data were collected through learning outcome tests to measure students’ cognitive achievement and observation sheets to assess student activity during the learning process. The results indicated that the implementation of the inquiry-based learning model improved students’ learning outcomes in each cycle, both in terms of learning mastery and student engagement. Therefore, the inquiry-based learning model is effective in improving the learning outcomes of fourth-grade elementary school students.